Su guía para beneficios de desempleo (Colorado Department of Labor and Employment, Unemployment Insurance Program, Colorado Department of Labor Employment, Unemployment Insurance Program, 2016)
Description Not Provided

Helpful facts about unemployment insurance benefits (Colorado Department of Labor and Employment, Colorado Department of Labor and Employment, [Division of Employment and Training], Colorado Department of Labor and Employment [Division of Employment and Training], 2009)
Description Not Provided

Ramona and her Father (Ramona Quimby, 4, 1, 1998)
When her father loses his job, seven-year-old Ramona Quimby thinks of ways to deal with the many problems that develop.
Payday , Ramona and the million dollars , The night of the jack-o'-lantern , Ramona to the rescue , Beezus's creative writing , The sheep suit , Ramona and the three wise persons.

Unemployment (Department of Labor & Employment, 2010)
Description Not Provided
Overview , Benefits estimator , Filing for unemployment insurance benefits online , Emergency unemployment compensation , Processing a claim , Unemployment insurance handbook for claimants , Getting paid.

Colorado Employment Security Act: rules and regulations pursuant thereto as amended by session laws of Colorado, 1963 (State of Colorado, Department of Employment, 1963)
Description Not Provided

Unemployment insurance and economic downturns (Issue brief, 20-13,, 2021)
This issue brief provides an overview of the Colorado unemployment insurance (UI) program, including UI benefits, funding, and solvency in the context of recent economic downturns. Economic downturns result in increased claims on regular state UI benefits. The speed and intensity of changes in UI claims during the COVID-19 Pandemic have been unprecedented.

A Christmas Memory (Thorndike Press, a part of Gale, a Cengage Company, Simon & Schuster Audio, Gallery Books, an imprint of Simon & Schuster, Inc, Gallery Books, 2022)
"It's 1967, and for young Richard it's a time of heartbreak and turmoil. Over the span of a few months, his brother, Mark, is killed in Vietnam; his father loses his job and moves the family to Utah; and his parents separate. When Richard is run down by bullies at his new school, he meets Mr. Foster, an elderly neighbor who chases off the bullies. Richard becomes fast friends with the man who inspires Richard's love for books and whose dog becomes his closest companion. With Mr. Foster's wisdom and kindness, Richard learns what truly matters: that forgiveness can heal the deepest wounds, and love endures long after the pain of loss subsides"--

Unemployment insurance handbook for employers (Colorado Department of Labor and Employment, Unemployment Insurance Operations, 2007)
Description Not Provided

Your guide to unemployment and getting paid benefits (Colorado Department of Labor and Employment, Unemployment Insurance Program, 2010)
Description Not Provided

Colorado's unemployment insurance program (Issue brief, 16-23,, 2016)
Unemployment insurance (UI) provides temporary, partial wage replacement to workers who have lost their jobs through no fault of their own.

MyUI employer user guide (Colorado Department of Labor and Employment, Unemployment Insurance Program, 2013)
Description Not Provided

How to record and report earnings while requesting payment of benefits (Colorado Department of Labor and Employment, 2015)
Description Not Provided

Federal unemployment assistance and the Reed Act distribution of 2002 (Issue brief, 03-04,, 2003)
Description Not Provided

Datos útiles acerca de los beneficios de desempleo (Colorado Department of Labor and Employment, 2015)
Description Not Provided

Colorado's unemployment insurance experience, 1980-2020 (REDI report, 2021, June,, 2021)
The federal-state system of unemployment insurance (UI) in the US, designed to protect laid-off workers, is coming under pressure for an overhaul following the pandemic. Using the US Department of Labor's Quarterly UI Data Summary, this report will outline a number of facets pertaining to Colorado's own UI experience since 1980.

What to do if you've lost your job (Service in action, no. 9.100,, 1983)
Description Not Provided

Do errors in benefit payments depend on the filing method? : the case of unemployment insurance in the United States (Working paper, 5,, 2016)
In 2014, US states paid a total of $36 billion in Unemployment Insurance (UI) benefits. Out of this amount, $4.5 billion were overpayments to beneficiaries. This estimate is based on audit data collected by the Department of Labor (DOL) which has historically monitored the UI system in each state for compliance with federal rules.

Coping with unemployment (Institute briefs, 4, issue 1,, 2002)
Description Not Provided

Layoffs and the state unemployment rate ([Colorado Department of Labor and Employment, Unemployment Insurance Program], 2003)
Description Not Provided

Colorado Unemployment Insurance Trust Fund summary report (Colorado Division of Unemployment Insurance, 2012)
Description Not Provided